Keterampilan Sosial Pengrajin Tatah Sungging Cilik Kepuhsari - Octavian Dwi Tanto; Hapidin Hapidin; Asep Supena (International Consortium of Education and Culture Research Studies, 2019)
This study aims to describe the findings social skills about The little craftsman of tatah sungging in Kepuhsari, Wonogiri. Those things observed; 1) description founds mony forms social skills about The little craftsman of tatah sungging in Kepuhsari, 2) description founds on the process of the forms social skills about The little craftsman of tatah sungging in Kepuhsari, and 3) description of supporting factors for the form about social skills of The little craftsman of tatah sungging in Kepuhsari. The subjects of this study were early childhood in the Kepuhsari region who were skilled in making tatah sungging works. This research is a qualitative research with an ethnographic approach. The results of this study indicate that the involvement of the litte craftsman on making tatah sungging works reflects their social skills such as the ability to work together, empathize, and communicate that is formed through exemplary and encouragement to produce precise work. It was also found that there were supporting factors such as philosophical values and perceptions of the Kepuhsari community towards tatah sungging art which stimulated the formation of social skills of the litte craftsman on the region.